2016
DOI: 10.1007/s00484-016-1167-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient air temperature, humidity, and wind speed on seminal traits in Braford and Nellore bulls at the Brazilian Pantanal

Abstract: The aim of this study was to evaluate the bioclimatic thermal stress assessed by Equivalent Temperature Index (ETI) and Temperature Humidity Index (THI) on Braford and Nellore bulls sperm quality during the reproductive seasons at the tropical region in the Brazilian Pantanal. We used 20 bulls aged approximately 24 months at the beginning of the study. Five ejaculates per animal were collected using an electroejaculator. Temperature, air humidity, and wind speed data were collected every hour from the automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…This indicates that although scrotal circumference was lower during winter and spring, the amount of sperm cells produced was not affected. European-breed bulls in the study, seemed to be more sensitive to heat stress and showed significantly lower sperm cell concentration during summer and autumn, when the mean ambient temperature reached an average of 30 o C. The negative effect of heat stress on spermatogenesis has been widely documented (Meyerhoeffer et al, 1985;Menegassi et al, 2016), and there are reports that mention that although ejaculate volume is not negatively affected by hyperthermia, initial motility, sperm concentration and total sperm counts decrease following exposure to temperatures above 29 o C and spermatogenesis is impaired at temperatures above 30 o C (Hansen, 2009). It is important to notice that semen characteristics are not immediately affected by high temperatures, and they do not return to normal until up to eight weeks following the end of heat stress (Hansen, 2009), which helps to explain the results of the lower sperm cell concentration found in European-breed bulls in the present study during the months of autumn that do not represent heat stress for the animals.…”
Section: Discussionmentioning
confidence: 73%
“…This indicates that although scrotal circumference was lower during winter and spring, the amount of sperm cells produced was not affected. European-breed bulls in the study, seemed to be more sensitive to heat stress and showed significantly lower sperm cell concentration during summer and autumn, when the mean ambient temperature reached an average of 30 o C. The negative effect of heat stress on spermatogenesis has been widely documented (Meyerhoeffer et al, 1985;Menegassi et al, 2016), and there are reports that mention that although ejaculate volume is not negatively affected by hyperthermia, initial motility, sperm concentration and total sperm counts decrease following exposure to temperatures above 29 o C and spermatogenesis is impaired at temperatures above 30 o C (Hansen, 2009). It is important to notice that semen characteristics are not immediately affected by high temperatures, and they do not return to normal until up to eight weeks following the end of heat stress (Hansen, 2009), which helps to explain the results of the lower sperm cell concentration found in European-breed bulls in the present study during the months of autumn that do not represent heat stress for the animals.…”
Section: Discussionmentioning
confidence: 73%
“…Previously studies by our group demonstrated that IRT can be used as an indirect technique to evaluate the effect of environmental stress on bull reproductive traits based on low scrotal TG and high OcT correlation (Menegassi et al., , 2016b). In rodents, the IRT technique is a good tool to assess temperatures on eyes, nose, internal and external ear suitable for detecting differences in heat stress in rabbits (Lima et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, thermographic image can provide a qualitative and quantitative map of the measured surface temperature that can be related to blood flow, distinct pathological conditions and reduced cellular activity (Ammer, ). Recently, it has been found that the use of IRT to evaluate environmental effects on sperm quality has a low correlation between TG and minor sperm defects that are also important for reproductive performance in bulls (Menegassi et al., 2016b). These distinctive characteristics on sperm parameters occur because the inflammatory lesions are related to changes in blood flow and this in turn can affect the scrotal skin temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the obtained THIs were considered below the temperature that impairs physiological disequilibrium due to thermal stress in animals, and thus it is likely that neither temperature nor humidity was high enough to cause testicular damage that may lead to direct consequences on testicular shape [13]. Recently, Brangus breed bulls showed a mean testicular gradient of 4.2, indicating a higher temperature gradient compared to Nelore (2.1) and Braford (3.3; 3/8 Nelore x 5/8 Hereford) bulls evaluated at the Pantanal region of Brazil [17]. The Braford breed is a mix of Bos taurus and Bos taurus indicus (3/8 Nelore x 5/8 Hereford), showing a significant adaptation to tropical and subtropical regions and presenting higher genetic potential to improve productivity efficiency.…”
Section: Discussionmentioning
confidence: 99%